Les acteurs territoriaux au défi de l'insertion Vers le territoire capacitant ? - Balzani, Bernard; Cervera, Melaine; Guèye, Khoudia; Houot, Isabelle; Marcandella, Elise; Starck, Sylvain; Wannenmacher, Delphine (RESSOR, 2022)
How can we understand public action in the field of social and professional inclusion? How can we measure changes and assess their impact on local areas? How can we address the needs of people who are ""furthest away"" from social and professional qualifications, or those who are ""invisible"" in terms of integration schemes? In other words, how can we work to ensure that everyone can participate in social and economic life at local level?